PENDUGAAN ZONA AKUIFER DENGAN METODE GEOLISTRIK RESISTIVITY KONFIGURASI SCHLUMBERGER DI DESA JENETALLASA KECAMATAN BANGKALA KABUPATEN JENEPONTO - Musriadi Musriadi; Ayusari Wahyuni; Andi Syam Rizal; Sahrul Sani Saparuddin; Andi Devi Sri Anjani (JFT : Jurnal Fisika dan Terapannya, 2019)
Springs are a problem in areas where geographic conditions are predominantly hot with low annual rainfall. Water is one of the basic needs for all living things on Earth, both plants, animals and especially humans. If there is a scarcity of spring sources, it is certain that daily activities are very disturbed. Scarcity of springs as happened in Jenetallasa Village greatly influences community activities in the Village. Prolonged drought results in increasingly severe water scarcity that occurs. Based on this problem, a field study was conducted to estimate the aquifer zone. Aquifers are a source of springs located in cavities brought under the surface of the ground which reminisce or flow. Aquifers themselves can be predicted without existence of drilling or excavation. Detection of aquifers can be done using geoelectric methods with different configurations. Our field study this time uses a schlumberger configuration with a length of 120 meters with an approximate depth of 60 meters below ground level.